Eksplorasi material daur ulang sampah polystyrene (PS) menggunakan metode material-driven design - Unzilatur Rohmah (Institut Seni Indonesia Yogyakarta, 2022)
Every year the Indonesian people are estimated to contribute 0.48-1.29 million metric tons of plastic waste to the oceans. Polystyrene (PS) takes more than 500 years to decompose naturally among the types of trash thrown away. For local producers, PS waste recycling requires more processing than other thermoplastic waste processing. On the other hand, PS waste processing is interesting to develop because of its shiny and transparent nature, so it is used as a jewelry product that cannot absorb a lot of waste. Therefore, this study aims to explore the uniqueness of PS recycling further so that it can be utilized optimally by local plastic waste recycling business actors. This study uses primary data collection methods such as observation, focus group discussions, and experiments. Experimental stages are carried out to find the proper treatment and get a unique texture and shape different from other materials. Furthermore, an analysis is made using the material-driven design method to see the value of the material. This analysis produces material visualization concepts such as uneven, imperfect, artless, translucent, and luxurious, which are suitable to function as vocal points for room styling. This study found that deficiencies in processing existing PS recycled materials can be overcome effectively and efficiently by melting 75 percent of the shredded plastic.